The Effect of Comparison of Starfruit and Carrot Porridge on Characteristics of Sheet Jam - Indriyani; sihotang, evachristina; Wulansari, Dian (Indonesian Food Science and Technology Journal, 2019)
Abstract-Sheet jam wasa modification of semi-solid topical jam made from fruits or vegetables, then concentrated with the aimedof forming solids or sheets. Jam generally usedripe fruit that was nottoo ripe and hada slightly sour taste. The purpose of this studyto determine the effect of starfruit and carrotporridge on the characteristics of sheet jam and to get a comparison of starfruit and carrot porridge on the characteristics of sheet jam. This study useda Completely Randomized Design (CRD) with 5 treatments, the comparisonedof starfruit porridgecarrotwere 0%: 100%, 25%: 75%, 50%: 50%, 75%: 25%, and 100%: 0% . Each treatment wasrepeated 3 times to obtain 15 experimental units. The parameterswereobservedin making sheet jam werewater content, vitamin C content, total dissolved solids (TPT), acidity (pH), degree of color, and organoleptic testing. The data obtained were analyzed with a variety of tests at the level of 1% and 5%. If the data obtained hada significant effect, then thedata would be continued withDNMRT (Duncan's New Multiple Range Test) at the 5% level. The researchresultsof starfruit and carrot porridge treatmentto the best sheet jams was 25%:75%with water content (36,53%), vitamin C (44,00 mg / 100 g of material), Total Dissolved Solids (42,20oBrix), pH (4,03), and degree of color (L=33,09, a=+9,31, b=+24,10 and0Hue=68,88). The best parameter of organoleptic testof sheet jam were the texturewassoft, slightly dense (2,92), color wasorange (4,32), plasticitywasnot easily broken (4.24), taste (3,60),overall acceptance (3,64)and aroma(3,60) according to panelists' judgment, which was somewhat preferred. Keywords- Carrots; sheet jam; starfruit.